Analysis of Implementation of Management Information Systems in the Tiket.com Application - Ritonga, Dendi Dwi Putra (Bina Bangsa International Journal of Business and Management, 2024)
Tiket.com is an online travel application that can help its users to book tickets through the internet, such as airplane tickets, train tickets, hotel reservations and so on. Most users of the Tiket.com application are dominated by those who need convenience in the traveling process. Management information systems are a technology that is very important and needed by business people to improve the quality and services provided to customers. The purpose of this research is to find out whether the implementation of the management information system in the Tiket.com application has been running optimally or not and how in the process of business activities. This research uses descriptive data analysis method by reading reference books, articles and journals made by experts to obtain accurate data so that data manipulation or other things do not occur. The subject of this research is an online travel application, namely Tiket.com. The results of this study indicate that the implementation of management information systems has been carried out optimally starting from disseminating information to its users so as to provide convenience and satisfaction to them. In addition, the implementation of a management information system on the Tiket.com application has a very good influence in supporting business activities.